A Population Pharmacokinetic Analysis Shows that Arylacetamide Deacetylase (AADAC) Gene Polymorphism and HIV Infection Affect the Exposure of Rifapentine - Francis, Jose (Antimicrob Agents Chemother, 2019)
Rifapentine is a rifamycin used to treat tuberculosis. As is the case for rifampin, plasma exposures of rifapentine are associated with the treatment response. While concomitant food intake and HIV infection explain part of the pharmacokinetic variability associated with rifapentine, few studies have evaluated the contribution of genetic polymorphisms. We evaluated the effects of functionally significant polymorphisms of the genes encoding OATP1B1, the pregnane X receptor (PXR), constitutive androstane (CAR), and arylacetamide deacetylase (AADAC) on rifapentine exposure. Two studies evaluating novel regimens among southern African patients with drug-susceptible pulmonary tuberculosis were included in this analysis. In the RIFAQUIN study, rifapentine was administered in the continuation phase of antituberculosis treatment in 1,200-mg-once-weekly or 900-mg-twice-weekly doses. In the Daily RPE study, 450 or 600 mg was given daily during the intensive phase of treatment. Nonlinear mixed-effects modeling was used to describe the pharmacokinetics of rifapentine and to identify significant covariates. A total of 1,144 drug concentration measurements from 326 patients were included in the analysis. Pharmacogenetic information was available for 162 patients. A one-compartment model with first-order elimination and transit compartment absorption described the data well. In a typical patient (body weight, 56 kg; fat-free mass, 45 kg), the values of clearance and volume of distribution were 1.33 liters/h and 25 liters, respectively. Patients carrying the AA variant (65.4%) of AADAC rs1803155 were found to have a 10.4% lower clearance. HIV-infected patients had a 21.9% lower bioavailability. Once-weekly doses of 1,200 mg were associated with a reduced clearance (13.2%) compared to that achieved with more frequently administered doses. Bioavailability was 23.3% lower among patients participating in the Daily RPE study than in those participating in the RIFAQUIN study. This is the first study to report the effect of AADAC rs1803155AA on rifapentine clearance. The observed increase in exposure is modest and unlikely to be of clinical relevance. The difference in bioavailability between the two studies is probably related to the differences in food intake concomitant with the dose. HIV-coinfected patients had lower rifapentine exposures.